Improving Public Health through a Free Health Screening Program for Early Detection of Diabetes Mellitus in South Jakarta - Julfilkar Adnan Irnu; Novia Faizatiwahida; Chery Delsia Azzahra; Zhyankha Zhyqrhy Sportuna; Istikomah Istikomah; Titha Widia Astuti; Imam Idrus (FKM UIN Sumatera Utara Medan, 2026)
Diabetes mellitus (DM) is a chronic disease with a steadily increasing incidence in Indonesia. Lack of public knowledge about prevention, early detection, and management of DM is a contributing factor to the high risk of this disease. This community service activity aims to increase public awareness and knowledge about diabetes mellitus and provide free health checks for early detection. The activity methods include counseling using leaflets and PowerPoint presentations, question and answer discussions, and random blood sugar and blood pressure checks. The activity was held at the Anggrek 2 Integrated Health Post (Posyandu), Duren 3 Community Health Center (Puskesmas Pembantu), Pancoran District, South Jakarta, with the participation of 35 participants. The results showed that 17.1% of participants had random blood sugar results ≥200 mg/dl (diabetes category), 14.3% were in the risk category, and 68.5% were within the normal range. Participants demonstrated high enthusiasm and increased understanding of the importance of early detection and a healthy lifestyle. This activity successfully raised public awareness of the importance of routine health checks and became the first step in preventing diabetes mellitus in the community.